Application of the Stress and Anxiety to Viral Epidemics-6 (SAVE-6) and Coronavirus Anxiety Scale (CAS) to Measure Anxiety in Cancer Patient in Response to COVID-19 - Ahn, Myung Hee; Lee, Jihoon; Suh, Sooyeon; Lee, Sangha; Kim, Hwa Jung; Shin, Yong-Wook; Chung, Seockhoon (Frontiers in Psychology, 2020)
This study investigated the usefulness of the 6-item Stress and Anxiety to Viral Epidemics (SAVE-6) scale and the Coronavirus Anxiety Scale (CAS) as tools to assess anxiety related to coronavirus disease (COVID-19) in cancer patients. A total of 221 patients with cancer responded to an anonymous online questionnaire between July 15 and August 15, 2020. The functional impairment of the patients was assessed using the Work and Social Adjustment Scale (WSAS), and the SAVE-6 and CAS were also applied. Among these 221 cancer patients, 110 (49.8%) had SAVE-6 scores ≥15 (mild anxiety) and 21 (9.5%) had CAS scores ≥5 (mild anxiety). Within the study population, 104 (47.1%) and 29 (13.1%) patients had WSAS scores ≥11 (moderate to severe functional impairment) and ≥21 (severe functional impairment), respectively. The correlations between the SAVE-6 and WSAS (p < 0.001) and CAS (p < 0.001) scores were statistically significant. The cut-off for the SAVE-6 was 15 points, while that for the WSAS was 11. Our results suggested that the SAVE-6 and CAS could be used to evaluate moderate and severe degrees of functional impairment related to mental health, respectively, in cancer patients during viral epidemics.